An Analytical Study of Jamiluddin Aali’s Dohas - Dr. Zeenat Bibi; Dr. Muhammad Nasir Afridi; Dr. Syed Aoun Sajid (Zaban-o-Adab, 2022)
Jamiluddin Aali was born in Delhi on January 1, 1924. After the establishment of Pakistan, he came to Pakistan from Delhi in 1947. During his life, he served in various positions. His first poetry collection was published in 1957 under the title "Ghazleen, Dohe, Git" with the title of Manzar Am Par Aya. His second poetry collection was published in 1957. Apart from ghazals, songs and poems, Aali also wrote national songs. There is a collection titled "Jiwe Jiwe Pakistan" that has spread to the public. Due to not only doha writing as a class, but also many new possibilities were revealed regarding the class.